The impact of turnitin to the student-teacher relationship - Scheg, Abigail G. (Journal of Interdisciplinary Studies in Education, 2013)
The relationship between student and teacher in the college composition classroom is directly effected by the implementation of a plagiarism detection service such as Turnitin. With more universities asking or mandating instructors to utilize these programs, instructors must be aware of both the pros and cons of Turnitin. The tensions of such a system come from the binaries that are created. The reliance on the stereotype that all college students would cheat, if given the opportunity. Utilizing my own experience as both a student and a faculty member required to use Turnitin. This article distinguishes the uses of the word plagiarism and the educational implications of both the term itself and its connotations. Using Frieres baking model and Foucaults concept of the panopticon, I analyze the positions of authority of both student and teacher in order to assess the effects of plagiarism to the composition classroom.